Penerapan Algoritma Fibonacci Codes Pada Kompresi Aplikasi Audio Mp3 Berbasis Dekstop - Jesica Martina Br. Panjaitan (Bulletin of Multi-Disciplinary Science and Applied Technology, 2021)
The need for greater storage capacity is the cause of the emergence of various compression techniques. Large data sizes result in wasteful memory and slow data transfer processes. Compression aims to reduce the size of the data to the smallest possible size. By doing compression, large data will be reduced in size so as to save storage capacity. This research was conducted with the aim and aim of analyzing the Fibonacci Codes algorithm in compressing audio files with the extension. Mp3 with comparison parameters of Ratio of Compression, Compression Ratio and Space Savings. Compression is done to reduce the bit size of the audio file. Because if the size of a large audio file is not compressed, there will be a delay when sending data. And also can meet the capacity of a storage memory. So with this compression system, it is hoped that it can overcome the problems that exist in society. On the compression algorithm that can be decompressed.